Female Entrepreneurs Role in Enhancing Halal MSME Growth and Profitability - Zulfatul Ihsan, Haifa; Rahmawati, Yunaita (Inovasi Analisis Data, 2025)
Objective: This paper investigates the underlying mechanisms by which entrepreneurial competence, networking, gender, and marketing capability influence business growth via innovation adoption.Methods: This study was quantitative, and data collection used a structured questionnaire among small, medium microenterprises Halal certified. Hypothesized relationships were tested using regression and mediation analyses.Results: Results show that marketing capability has the most powerful effect on business growth, and all four factors are statistically significant. Innovation adoption partially mediates these relationships: much of their impact on growth is accounted for by the ways in which they affect new processes, products, and business models. The research supports a complex view of resources and environments that are involved in the dynamic reformation between internal capability and external relationships through learning faster from innovation for competitive advantage and market enlargement.Novelty: This study contributes to the theoretical development of a new integrated model, which places adoption of innovation as an intra-mechanism transforming entrepreneur resources into growth, and for the first time, developed within a dynamic,c ethics-rooted Halal industry context. Insightful procedures for strategic organizing.Research Implication: The outcomes contribute a validated model which policymakers and business developers can use to create integrated interventions that simultaneously reinforce core competences, strategic networks, and marketing capabilities aimed at stimulating an innovation culture in order to enhance sustainable business performance and sectoral resilience.